A three-sided story: a biosystematic revision of genus Datura reveals novel tropane alkaloids for the first-time in certain species - Abeer Al-Andal; Mohamed Ewas; Mohamed Ewas; Abd El Raheim M. Donia; Asmaa M. Radwan; Mohamed N. S. Suliman; Elsayed Nishawy; Ahmed El-Shabasy; Eman Khames (Frontiers in Plant Science)
IntroductionDatura, long considered an medicinal plant, represents a prospective source for discovering novel drugs for modern medicine. The Egyptian flora encompasses six Datura genotypes, including D. innoxia, D. ferox, D. metel and three forms of D. stramonium (stramonium, tatula and inermis). However, the taxonomic status of Datura genus remains controversial.MethodsOur study aims to clarify the phylogenetic relationships among Egyptian Datura via contemporary molecular taxonomy techniques, including ISSR, SCoT, CDDP, as well as cytogenetics assessment, and chemical taxonomy, using total- and tropane-alkaloid and UV spectroscopic pattern.ResultsBased on our results, the three forms of D. stramonium (stramonium, tatula and inermis) are closely related taxa, although there were some significant differences, suggesting the need to upgrade inermis to level of subspecies (Datura stramonium subsp. Inermis). The GC-MS results identified 31 tropane alkaloids. Out of which, seven were described in a qualitative manner in genus Datura, which enhances these genotypes’ medical and economic value. Expression level of the genes PMT, TR1, TR2, H6H, HDH and AT4 influenced the tropane alkaloids accumulation within the genotypes examined.DiscussionTo date, this is the first study to identify the evolutionary relationship of the genus Datura combining molecular and chemical taxonomy, and to quantify the TAs and the genes involved in their biosynthesis among Datura genotypes.ConclusionThis study is significant since drug development strategies and enhanced therapeutic usage of Datura heavily depend on comprehensive knowledge of the species and subspecies’ molecular and phytochemical variability.